Different types of abstract concepts: evidence from two neurodegenerative patients. Issue 3 (4th May 2021) - Catricalà, E.; Conca, F.; Borsa, V.M.; Cotelli, M.; Manenti, R.; Gobbi, E.; Binetti, G.; Cotta Ramusino, M.; Perini, G.; Costa, A.; Rusconi, M.L.; Cappa, S.F.
ABSTRACT: The observation of neurological patients showing selective impairments for specific conceptual categories contributed in the development of semantic memory theories. Here, we studied two patients (P01, P02), affected, respectively, by the semantic variant of Primary Progressive Aphasia (sv-PPA) and Cortico-Basal Syndrome (CBS). An implicit lexical decision task, including concrete (animals, tools) and abstract (emotions, social, quantity) concepts, was administered to patients and healthy controls.P01 and P02 showed an abolished priming effect for social and quantity-related concepts, respectively. This double dissociation suggests a role of different brain areas in representing specific abstract categories, giving insights for current semantic memory theories.